Effects of low level laser therapy on the gingival and periodontal tissues in orthodontic patients - Kumar , Kishore (2017)
The aim of this split-mouth, experimental, randomized clinical trial was to study the effects of low-level lasers therapy (LLLT) on periodontal indices as an adjunct of orthodontic treatment induced gingivitis and periodontitis in initial phase of orthodontic treatment. The study was conducted among forty patients who were scheduled for fixed orthodontic treatment. After clinical examination, all teeth were scaled. The clinical parameters, plaque index (PI), gingival index (GI), bleeding on probing (BOP) and probing depths (PD) were measured and LLLT was applied at every visit i.e. 0, 1, 2, 3, 4, 5 and 6 months on one side of each jaw. The other side of the jaw was considered as control. The test side was treated with low-level lasers having wavelengths of 940 nm. PI, GI, BOP and PD for the research was recorded at 0 (T1), first (T2), third (T3) and sixth (T4) visit. Repeated measure ANOVA showed that there was statistically significant inter group and intra group differences (<0.05) where GI, BOP and PD scores generally increased along the evaluation period in both groups. The scores increased more in the control group. Moreover, pairwise comparisons based on the Paired t test showed that, there was no significant difference in T1 stage of evaluation of the GI and BOP when compared between LLLT and control group. However, both groups were showed significant differences in T2, T3 and T4 stage of evaluation of the GI and BOP. Moreover, pairwise comparisons based on the Paired t test showed that, there was no significant difference in T1 and T3 stages of evaluation of the PD when compared between LLLT and control group. However both groups were showed significant differences in T2 and T4 stage of evaluation of the PD. Additional treatment with LLLT reduced the orthodontic treatment induced gingivitis and periodontitis.